Astronomy - Firth, Rachel; Owen, Lucy (Usborne Publishing Ltd. London, 2004)
On a clear night, you can see thousands of stars in the sky. But they are just a tiny part of what's out in space. In this book, you'll discover some of the amazing things that are out there, many of which you can see with just a pair of binoculars or a small telescope. This book will give you practical advice about how to find them, as well as the answers to hundreds of questions, What are constellations and how can you find them? Why do the stars seem to change position from one night to the next? What happens when there's an eclipse? What causes meteor showers?
Keywords: Astronomy